The Global Burden and Trends of Legionella spp. Infection-Associated Diseases from 1990 to 2021: An Observational Study - Yonghong Zhong; Linfeng Shen; Yan Zhou; Yibo Sun; Xiaofang Fu; Huaqiong Huang (Journal of Epidemiology and Global Health)
Abstract Background Legionella infections are a major global health issue, yet there’s limited research on their impact and trends. We aimed to systematically analyzed the long-term trends in Legionella spp. infection-associated diseases (LSIADs) burden from 1990 to 2021. Methods Age-standardized disability-adjusted life years (ASR-DALYs) and age-standardized death rates (ASDRs) of LSIADs from 1990 to 2021 were accessed from the Global Burden of Disease (GBD) 2021, which utilized the Bayesian hierarchical meta-regression tool and the Cause of Death Ensemble model to estimate these metrics. Trends in disease burden across age, sex, region, and Socio-Demographic Index (SDI) levels were estimated using annual percentage changes (EAPCs) and annual percentage changes (APCs). Results Globally, the ASR-DALYs and ASDRs for LSIADs in 2021 were 24.74 and 0.86 per 100,000, respectively, with the highest rates observed in regions with low SDI. From 1990 to 2021, while the overall burden of LSIADs showed a downward trend, the highest ASR-DALYs (101.85 per 100,000) and ASDRs (8.15 per 100,000) were observed in individuals over 70 years of age, accompanied by a corresponding increase in deaths (EAPCs = 0.17%, 95% CI: 0.09–0.26%). Furthermore, increases in ASR-DALYs and ASDRs for LSIADs were also noted among those aged 15–49 years (EAPCs = 0.43% and 0.57%, respectively) and those aged 50–69 years (EAPCs = 0.14% and 0.09%, respectively). Conclusion Higher disease burdens and increasing trends have been observed in specific age groups and regions, which require the implementation of water quality management plans, enhanced readiness of health facilities, and improved sanitation infrastructure.